Monkeypox viral disease outbreak in non-endemic countries in 2022: What clinicians and healthcare professionals need to know - David Onchonga (Elsevier, 2022)
An outbreak of monkeypox Viral Disease in non-endemic countries in May 2022 is increasingly spreading. Clinicians and other healthcare professionals need to understand the aetiology and characteristics of the monkeypox pathogen and illness. By familializing themselves with these characteristics, they can map out the outbreak and roll out necessary public health mitigation measures to curb the spread. This short communication presents a summarized message regarding the aetiology, mode of transmission, clinical features, risk factors, diagnosis, treatment, and prevention of monkeypox viral disease. Considerations for surveillance and reporting have also been highlighted.